Perancangan Interior International Culinary School di Surabaya - Edward Leonard; Andereas Pandu Setiawan (Intra, 2018)
Food as the basic needs of human life has made the culinary world a developing business. With the design of culinary school facilities, the objective of this design project is to create an interior environemnt that can support the quality learning activities that can compete with the contemporary culinary world. This culinary school design project was inspired by the concept of "Back to Nature," which was implemented in the forms and colors containing elements of Nature, such as use of the wood, concrete and natural stone on the walls, furniture, roof, and floor. This concept was chosen in order to be able to solve the design problems such as the lack of space, the unclear grouping and circulation, and the unattractive interior atmosphere.